The Influence of Capital Expenditures, Government Size, and Audit Opinions on Disclosure of Government Financial Statements of Nusa Tenggara - Prapti Ningsih (Pusat P2M Politeknik Negeri Batam, 2020)
This study is a quantitative study that aims to examine the effect of capital expenditure as measured by total expenditure transformed to Ln capital expenditure, Government Size measured by total asets transformed to Ln total asets and Number of SKPDs, and audit opinion measured by grading levels opinion obtained by the Regency / City in Nusa Tenggara. The population in this study were all districts / cities in Nusa Tenggara 2016-2018, the sample in this study used a saturated sample. Testing the hypothesis in this study using Multiple Regression Analysis with the SPSS program. Hypothesis testing results show that (1) capital expenditure has a significant effect on the disclosure of local government financial statements (2) government size on asets does not have a significant effect on the disclosure of local government financial statements (3) government size on the number of SKPD does not significantly influence the disclosure of government financial statements regional (4) audit opinion has a significant effect on the disclosure of local government financial statements